Patterned Thermoresponsive Microgel Coatings for Noninvasive Processing of Adherent Cells - Uhlig, Katja; Wegener, Thomas; He, Jian; Zeiser, Michael; Bookhold, Johannes; Dewald, Inna; Godino, Neus; Jaeger, Magnus; Hellweg, Thomas; Fery, Andreas; Duschl, Claus (Biomacromolecules, 2016)
Cultivation of adherently growing cells in artificial environments is of utmost importance in medicine and biotechnology to accomplish in vitro drug screening or to investigate disease mechanisms. Precise cell manipulation, like localized control over adhesion, is required to expand cells, to establish cell models for novel therapies and to perform noninvasive cell experiments. To this end, we developed a method of gentle, local lift-off of mammalian cells using polymer surfaces, which are reversibly and repeatedly switchable between a cell-attractive and a cell-repellent state. This property was introduced through micropatterned thermoresponsive polymer coatings formed from colloidal microgels. Patterning was obtained through automated nanodispensing or microcontact printing, making use of unspecific electrostatic interactions between microgels and substrates. This process is much more robust against ambient conditions than covalent coupling, thus lending itself to up-scaling. As an example, wound healing assays were accomplished at 37 °C with highly increased precision in microfluidic environments. (Figure Presented).
CRIS-Team Scopus Importer:2023-03-20